Co-dependency pada Tokoh Ibu Tunggal dan Anak Laki-Lakinya dalam Film Mother - Rahmawati, Devina Nur; Srimulyani, Nunuk Endah (Japanology: The Journal of Japanese Studies, 2023)
Co-dependency can occur in any kind of relationships, such as husband and wife, friends, and even parents and children. This phenomenon is being represented in media, such as movie titled Mother by Tatsushi Omori. This movie is chosen to be research object with the aim of analyzing the depiction of codependency in a single mother named Akiko and her son named Shuhei. The research used qualitative method with descriptive analysis. The results showed that despite the differences in co-dependency behaviors that Akiko and Shuhei have, there are the same goals and desires, both are equally dependent and need each other. Although Akiko is more dominant and harms Shuhei a lot, it does not make Shuhei think of leaving Akiko. The relationship between mother and son, who have always lived together and are accustomed to each other's nature, makes them even more bonded and attached which then creates a co-dependency that is difficult to end. No matter what the circumstances, these two will never want to leave each other or be left behind.